Prediction of internet addiction based on information literacy among students of Iran University of Medical Sciences - Mostafa Langarizadeh; Majid Naghipour; Seyed Mohsen Tabatabaei; Abbas Mirzaei; Mohammad Eslami Vaghar (Electronic Physician, 2018)
Background: A considerable group of internet users consists of university users; however, despite internet benefits and capabilities, internet overuse is a threat to societies especially to young people and students. Objective: The objective of this study was to determine the predictive role of information literacy in internet addiction among students of Iran University of Medical Sciences during 2016. Methods: This analytical cross-sectional study was conducted in Iran University of Medical Sciences in 2016. Using stratified random sampling method, 365 students from different disciplines were selected. Measuring tools included the Information Literacy Questionnaire, the Yang Online Drug Addiction Scale and the General Health Questionnaire. The collected data were analyzed by Pearson product-moment correlation, independent samples ttest and multiple linear regression using SPSS version 22. Results: According to this study, 31.2% of students had internet addiction (29.9% were mildly addicted and 1.3% had severe addiction). There was a significant and inverse relationship between higher information literacy and internet addiction (R= -0.45) and (p<0.001). The predictor variable “Information literacy” explained 20% of the variation in the outcome variable “Internet addiction”. Conclusion: Students play a substantial role in promoting the cultural and scientific level of knowledge in society; the higher their information literacy, the lower the level of Internet addiction, and consequently the general health of society will improve. It seems that wise planning by authorities of Iran's universities to prevent internet addiction and to increase information literacy among students is needed.